Pembelajaran Kooperatif dengan Media Virtual untuk Peningkatan Penguasaan Konsep Fluida Statis Siswa - Nina Nisrina; Gunawan Gunawan; Ahmad Harjono (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
Physics is contain a lot of abstract concept.this thing arise studentÃ¢â¬â¢s difficulty in learning physics individually. This difficulty can be solved by educatorsÃÂ  with using the method of cooperative learning on teaching their pupil. Beside of that, on teaching abstract concept can be helped by using virtual media. Because of that, this research is aim to test the effect of cooperative learning with virtual media toward the studentÃ¢â¬â¢s conceptual understanding in physics on static fluid matter. Pre-test and post-test was gived to experiment and control class. The instrument of the test is conceptual test which consist of six cognitive aspect. The result show that the cooperative learning with virtual media increased studentÃ¢â¬â¢s conceptual understanding in static fluid and significantly increased at sub-matter Archimedes law and fluid pressure. This result also showed the increase of studentÃ¢â¬â¢s cognitive abilty on experiment class, but one of cognitive aspect C6 (create), control class more better than experiment class.